PENGEMBANGAN INDUSTRI MANUFAKTUR MELALUI KOMPUTERISASI - Adil, Malikul (JURNAL TEKMAPRO, 2007)
Abstract To development of industrial engineering in computerization must have been manufacturing and management systems and its application in company organization. Manufacturing system as useful reference by  business scientists and practitioners or anyone who seeks for information to develop Enterprise Resource Planning (ERP) through close loop process Manufacturing Resource Planning (MRP II). This article provides in-depth knowledge of the Enterprise Resource Planning methodology and its application in manufacturing company.   Key words   :   Material Requirement Planning (MRP I), Manufacturing Resource Planning (MRP II), Enterprise Resource Planning (ERP)